Takhrij Hadist tentang Riba - Hayatul Millah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2016)
Riba linguistically Ziyadah (extra). Another sense linguistically, riba means also grow and expand. Briefly on the language of usury has the meaning ‘to grow’ both of quality and quantity. While the term riba means making additional cost or capital vanity. Besides in Al-Qur’an, there are some hadiths also explaining usury, where we know that the hadith is one of the sources of law to explain in detail the Al Quran. In some traditions mentioned that the Prophet emphasized to Muslims for meninggalakan usury including; in the last mandate Hijjah 9th year 10 Hijri, the Prophet emphasized the attitude of Muslims towards usury. In a hadith mentioned “Remember that you will be facing your Lord and He would count the deeds. God forbid you take usury. Therefore, the debt must be eliminated as a result of usury. Capital (principal) you are your rights. You will not suffer taupun suffered injustice